Interactive 3D multimedia content : models for creation, management, search and presentation - Cellary, Wojciech; Walczak, Krzysztof (2012)
Describes the research results in the areas of modelling, creation, management and presentation of interactive 3D multimedia content. This title addresses such issues as: database modelling of 3D content, security in 3D environments, describing interactivity of content, searching content, visualization of search results, and more